Public Service Innovation In Investment Services And One Door Integrated Services Badung Regency Bali Province - Dwi Widari, Ni made; Yuslinda Dwi Handani; Abubakar Eby Hara (Universitas Muhammadiyah Jember Press, 2023)
Bali Province, Badung Regency is one of the regions of Indonesia by providing public services as stated in Law Number 25 of 2009 which states that public services are a series of activities in fulfilling the service needs of the population for goods, services and/or administrative services provided by the administrator. public service. The Badung Regency Government through the Investment Service and One-Stop Integrated Services of Badung Regency through e-government made a breakthrough to create a new innovation called the LAPERON innovation which provides permit and non-permit services in the form of commercial and non-commercial licensing. The aim of this research is to describe the typological product form of public service innovation in Badung Regency based on the typological dimensions of public service innovation according to Muluk (2008) and the dimensions of public service innovation according to Rogers (2003). The method is descriptive qualitative. Sources of data through interviews and documentation selection of informants by technique purposive. To check the validity of the data used data triangulation. The data analysis technique was carried out using an interactive analysis model (Miles and Huberman). The results of this study indicate that the typology of public service product innovation runs optimally. However, of the five dimensions of public service innovation, only one does not meet these dimensions. The dimension in question is the observability dimension. There is a lack of service delivery,culture shock, and socialization.